Photocatalytic disinfection of bacteria under visible light irradiation by BiFeO3 photocatalyst. Issue 1 (April 2021) - Daub, N A; Aziz, F; Mohd Zain, N A; Lau, W J; Yusof, N; Salleh, W N W; Jaafar, J
Abstract: BiFeO3 nanoparticles was synthesized by sol gel auto combustion. The as-synthesized BiFeO3 were characterized by X-ray diffraction (XRD), UV-Vis diffuse reflectance spectra (DRS) and Brunauer-Emmett-Teller (BET) analysis. The disinfection activities towards Gram-positive Staphylococcus aureus (S.aureus) were examined under visible light irradiation. The results showed a complete inactivation of 3 × 10 6 CFU/mL S.aureus was achieved within 20 min. The disruption of bacterial cell structure was observed by Transmission electron microscope (TEM). The cells were severely damaged after being exposed to BiFeO3 under visible light irradiation. Hence, the results demonstrated the potential application of perovskite-type photocatalyst, BiFeO3 in photocatalytic disinfection of various microorganisms.